POLA ASUH DAN AKTUALISASI DIRI: SUATU INTERNALISASI FILOSOFI PENDIDIKAN RABINDRANANTH TAGORE DALAM POLA PENGASUHAN ANAK - Effendi, Yusuf (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2024)
Parenting patterns are the basis that influence a child's growth and development. The parenting model applied to children will determine how children develop in physical, psychological and social aspects. The focus of the research will refer to efforts to internalize Rabindranath Tagore's educational philosophy which includes five points, namely freedom, harmony, active communication with man and nature, creative self-expression and internationalism into a practical parenting model. This research uses a qualitative research method with a library research approach which is sharpened by descriptive studies. This research found that the five points of Tagore's method, if internalized in a parenting pattern model, will produce a new parenting pattern model that produces a method that emphasizes self-respect for children, children's freedom to actualize themselves, instilling an attitude of caring for the natural and social environment in children and emphasizing the role of parents in providing motivation and appreciation.